Gradual Downregulation of Protein Expression of the Partner GABABR2 Subunit During Postnatal Brain Development in Mice Defective of GABABR1 Subunit - Masaki Fukui; Shusuke Ozawa; Noritaka Nakamichi; Ryota Nakazato; Takeshi Takarada; Yukio Yoneda (Elsevier, 2011)
We have previously shown the functional expression of GABAB receptors (GABABR) composed of GABABR1 and GABABR2 subunits with ability to promote proliferation and neuronal differentiation in cultured neural progenitor cells (NPC) isolated from embryonic mouse brains. In this study, we evaluated postnatal changes in the expression profiles of different markers for progenitor, neuronal, astroglial, and microglial cells in brains of GABABR1-null mice. Consistent with undifferentiated murine NPC cultured with epidermal growth factor, a significant and selective decrease was seen in mRNA expression of the proneural gene Mash1 in brains of GABABR1-null mice at 1 day after birth. The expression of several NPC marker proteins was similarly decreased in brains of both wild-type and GABABR1-null mice from 1 to 7 days after birth, while slight changes were induced in both mRNA and proteins for neuronal, astroglial, and microglial markers between wild-type and GABABR1-null mouse brains within this developmental stage. In particular discrete brain structures of adult GABABR1-null mice at 56 days after birth, a significant decrease was seen in neuronal marker protein levels along with a significant increase in both astroglial and microglial marker protein expression. Although no significant difference was found in mRNA expression of the partner GABABR2 subunit between wild-type and GABABR1-null mouse brains, GABABR2 subunit protein levels were gradually declined during postnatal development within 56 days after birth in GABABR1-null mouse brains. These results suggest that GABABR2 protein levels are closely correlated with the partner subunit GABABR1 protein levels in mouse brains during postnatal development in vivo. Keywords:: neural progenitor cell, GABAB receptor (GABABR), brain development, GABABR1 subunit, GABABR2 subunit